(untitled) (Research, Society and Development, 2023)
This article aims to implement a management system for ordnance, to understand how this can help the 7th Military Police Battalion of Pará (7th BPM-PA) to control its material and how the public sector, especially the Military Police, needs to innovate and use technological tools to improve its performance, and that the implementation of Integrated Management Systems (ERP) can bring significant benefits, such as improvement in general administration and process efficiency. In addition, based on a qualitative face-to-face research, it describes the process of conception, idealization, modeling, and development of a war management system, aiming to automate the process of managing weapons and equipment, allowing users to perform the necessary activities in a simple and effective way, without worrying about spreadsheets and other outdated methods, optimizing time and resources, as well as providing quick and easy access to data and reducing spending on graphic materials.